PENERAPAN TEKNIK PASAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 1 SIPORA TAHUN PELAJARAN 2012-2013 - Susanti, Dewi; Rismen, Sefna; Anggraini, Villia (Pendidikan Matematika, 2014)
ABSTRACTÂ The background of this research is the comprehension of the studentsâ mathematical concept that are still low. Not only that, but also the process of learning is still contred to the teacher it self. The purpose of this researchÂ  is to know about comprehension of the studentsâ mathematical concept by applaying Market technique toward comprehension of mathematical concept is better than studentsâ conventional learning at the eight grade SMPN 1 Sipora Kabupaten kep.Mentawai. The kind of this research is experiment reserch. The population of this research is the eighth grade students of SMPN 1 Sipora Kep. Mentawai who registered in 2012/2013 academic year. The sample classes that choosen are two Â classes, where VIII.1class as class experimental class and the VIII.2 is control class. The instrument of this research is the concept comprehension test in essay that has reliability 0,8883. Based on the data analysis, mean of Â experimental class was 80,61 and class control was 71,03. can Â concluded that the comprehension of the studentsâ mathematical concept by applaying the market technique toward comprehension ofÂ  mathematical concept is better than conventional learning at the eight grade SMPN 1 Sipora Kabupaten Kepulauan Mentawai.